Physico-Chemical Factors of Lubilanji River (Oriental Kasaï Province, Democratic Republic of the Congo) - André Kabamba Mulangu; Isaac Ekyamba Shabani; Alidor Busanga Kankonda (Annals of Environmental Science and Toxicology - Peertechz Publications, 2017)
Background and aim: Fishing and fi sh farming sectors currently face major challenges related to the lack of knowledge of data on the physico-chemical quality of water bodies from Lubilanji River. This investigation intended to determine the physico-chemical parameters of Lubilanji River. Methods: Fourteen physico-chemical parameters were studied in Lubilanji River including temperature, turbidity, transparency, conductivity, pH, alkalimetric title, total hardness, calcium, nitrate, phosphate, oxygen dissolved, depth, width and velocity. Results: The analysis showed that average value of transparency in all stations is of 54.09 cm with coefficient of variation of 31.84%. While the average of water velocity is 91.30 m/s with coefficient of variation of 49.80% in all stations. The parameters like water velocity, turbidity, temperature, calcium and pH indicated their low infl uence on stations. According to the results found, the Libilanji River should be rich in ichthyological biodiversity.